1980
DOI: 10.1139/o80-006
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme I of the phosphoenolpyruvate: sugar phosphotransferase system of Escherichia coli. Purification to homogeneity and some properties

Abstract: Enzyme I of the phosphoenolpyruvate - sugar phosphotransferase system (PTS) has been purified to homogeneity from Escherichia coli. A merodiploid strain P650 which had an extra copy of the gene for enzyme I resulting in a twofold increase in the amount of activity was used. The enzyme is a dimer of 67 000 +/- 5000 molecular weight subunits. At low protein concentration and 4 degrees C the monomer predominates, while at room temperature the dimer predominates. At higher protein concentrations (2 to 10 mg) this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
90
0

Year Published

1982
1982
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(102 citation statements)
references
References 0 publications
12
90
0
Order By: Relevance
“…Treatment of EI with DNase and RNase, followed by several washing steps in an Amicon ultrafiltration apparatus with an UM-20 filter, changed the UV spectrum in that the maximum absorbance appeared at 277 nm and the minimum absorbance at 252 nm. In the modified procedure, EI eluted from the DEAE-cellulose column Whatman) a dimer molecular weight of 134000 (Misset et al, 1980;Waygood & Steeves, 1980)]. This experimental value agrees well with the extinction coefficient calculated by Waygood from the amino acid composition of enzyme I: eig$$'L = 4.4 (Waygood et al, 1980).…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…Treatment of EI with DNase and RNase, followed by several washing steps in an Amicon ultrafiltration apparatus with an UM-20 filter, changed the UV spectrum in that the maximum absorbance appeared at 277 nm and the minimum absorbance at 252 nm. In the modified procedure, EI eluted from the DEAE-cellulose column Whatman) a dimer molecular weight of 134000 (Misset et al, 1980;Waygood & Steeves, 1980)]. This experimental value agrees well with the extinction coefficient calculated by Waygood from the amino acid composition of enzyme I: eig$$'L = 4.4 (Waygood et al, 1980).…”
Section: Resultssupporting
confidence: 82%
“…The mechanism of Scheme I1 differs from the one presented by Waygood & Steeves (1980). They concluded that Scheme I is the proper mechanism for the enzyme I catalyzed phosphorylation of HPr.…”
Section: Phosphoryl-groupmentioning
confidence: 88%
See 1 more Smart Citation
“…of EI for PEP) range from 0.2 to 0.4 mM (43,65), and values of EI ⅐ P for Pyr range from 1.5 to 3 mM (66). Furthermore, the equilibrium constant for the above reaction is 1.5 (44).…”
Section: Derivation Of Rate Constants For Pts Reactionsmentioning
confidence: 99%
“…First, there was a large discrepancy between reported K m values for MeGlc (170 M in vivo and 6 M in vitro) (41), whereas the K m values for glucose agreed much better (see above). Second, the K d value (Equation 43) has only been determined for glucose (42) (also see "Discussion").…”
Section: Appendixmentioning
confidence: 99%